Who makes the decision? Malaysian healthcare professionals' views on prostate cancer treatment - Lee, Yew Kong; Lee, Ping Yein; Cheong, Ai Theng; Ng, Chirk Jenn; Abdullah, Khatijah Lim; Ong, Teng Aik; Abdul Razack, Azad Hassan (Society for Medical Decision Making, 2014)
Purpose: This study aimed to explore the views of Malaysian healthcare professionals (HCPs) on the roles of various stakeholders who were involved in making decisions about prostate cancer treatment. Method: Four in-depth interviews and three focus group discussions were conducted with HCPs from government and private hospitals in Malaysia between December 2012 and March 2013. HCPs consisted of private urologists (n=4), government urologists (n=6), urology trainees (n=5), government policy maker (n=1) and oncologists (n=3). There were 16 male and three female participants. Trained researchers used a topic guide to guide the interviews which were audio-recorded, transcribed verbatim, checked and managed with Nvivo 10 software. Thematic approach was used to analyse the data. Result: Three parties were involved in the decision making process: HCPs, patients and family. Patients who did not understand prostate cancer and its treatment had difficulty in making decisions. These patients tended to leave the decision to the HCPs. Some patients made their own treatment decision. Some patients avoid asking too many questions to avoid the possibility of being influenced towards one option by their HCP. HCPs would leave the final say to the patient because of three reasons: to avoid patients’ regret (“patient will not be happy at the end of the day”); wanting the patient to “balance what they wanted and what was the reality of each option”; and knowing there was no single best treatment option. The family members, especially children, made the decision for some patients. This may be due to Malaysia’s close-knit family culture where patients were concerned about their children’s emotions. While some patients were able to make their own decisions for non-invasive treatment (e.g. hormonal treatment), they would like to involve their family if they were considering surgery. HCPs observed that patients rarely involved their wives in decision making. Conclusion: Decision making during prostate cancer treatment involves three parties; HCP, patient and family. The decisional roles depend on the patients personal preferences, understanding of the illness, and the family dynamics.